Relación de fatiga pandémica y motivación laboral en estudiantes de posgrado de una universidad nacional peruana - Aldave Campos, Elizabeth Juana Ruth (2023)
The aim of this study was to determine the relationship between pandemic fatigue and workplace motivation in graduate students from a state university in Peru in 2022. A correlational, non-experimental, simple and descriptive quantitative study was performed, based on a structured questionnaire administered to the demographic group from the study, with a sample of 30 students. Regarding reliability, Cronbach's alpha was 70.4% for the validity of the 21-item questionnaire used in the pilot prototype. The findings showed that 60.0% of survey respondents reported that they sometimes felt work-related stress in the workplace. 66.7% of survey respondents reported that they sometimes felt anxiety during working hours, while 66.7% reported that they sometimes felt some physical and emotional tension during working hours. Meanwhile, 46.7% reported that they had a harmonious relationship with their superior. In addition, 66.3% reported that they have good social relationships with their peers; lastly, 53.3% reported that they felt satisfaction in their current position. Regarding the correlation analysis for variable association, a value of -.586 was obtained, with p < .001, therefore confirming the general hypothesis. It is concluded that pandemic fatigue has a moderate correlation with employee motivation, considering the coefficient value of 0.586. However, there are strategies that can be implemented to mitigate its effects.